2016
DOI: 10.1021/acs.jmedchem.5b01106
|View full text |Cite
|
Sign up to set email alerts
|

Development of Heat Shock Protein (Hsp90) Inhibitors To Combat Resistance to Tyrosine Kinase Inhibitors through Hsp90–Kinase Interactions

Abstract: Heat shock protein 90 (Hsp90) is a ubiquitous chaperone of all of the oncogenic tyrosine kinases. Many Hsp90 inhibitors, alone or in combination, have shown significant antitumor efficacy against the kinase-positive naïve and mutant models. However, clinical trials of these inhibitors are unsuccessful due to insufficient clinical benefits and nonoptimal safety profiles. Recently, much progress has been reported on the Hsp90-cochaperone-client complex, which will undoubtedly assist in the understanding of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 157 publications
1
44
0
Order By: Relevance
“…Heat shock proteins (Hsps) are a family of molecular chaperones that consist of Hsp100, Hsp90, Hsp70, Hsp60 and many other smaller Hsps (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock proteins (Hsps) are a family of molecular chaperones that consist of Hsp100, Hsp90, Hsp70, Hsp60 and many other smaller Hsps (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Hsp90 has long been recognized as a viable molecular target for cancer treatment [13]. The majority of Hsp90 inhibitors currently in the clinic are Hsp90 N-terminal inhibitors that interact with the ATPase binding site in the N-terminal of Hsp90 structure [14][15][16]. The earlier Hsp90 inhibitors including the natural product geldanamycin and its analogues (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…HSP90 is an important molecular chaperone for protein folding, transmission, and intracellular localization, in both normal and tumor cells (16,17). HSP90 is an important regulator of cell growth and survival, as well as being essential for the activity of a wide range of key oncogenic proteins, including kinases, transcription factors, and suppressor proteins (17,18). Many HSP90 client proteins are involved in processes such as proliferation, apoptosis, and cycle progression (16,18).…”
mentioning
confidence: 99%
“…HSP90 is an important regulator of cell growth and survival, as well as being essential for the activity of a wide range of key oncogenic proteins, including kinases, transcription factors, and suppressor proteins (17,18). Many HSP90 client proteins are involved in processes such as proliferation, apoptosis, and cycle progression (16,18). Several reports have analyzed HSP90 expression in solid tumors and found that HSP90 expression is correlated with clinical prognosis, (5,16,19,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation